Comprehension and acceptability of a patient information leaflet (pil) for antiretroviral therapy - Betty Mwingira; Ros Dowse (AOSIS, 2006)
The patient information leaflet (PIL) is recognised as playing a key role in informing patients about their medicines. The objectives of this research were to evaluate the readability and understanding of a PIL for the first-line ARV (antiretroviral) regimen available in the South African public health sector, and investigate its acceptability in the target Xhosa population. Opsomming Daar word algemeen aanvaar dat die pasiëntinligtingsblaadjie (PIB) 'n sleutelrol speel in die oordra van inligting ten opsigte van medikasie aan pasiënte. Die doelwitte van hierdie navorsing was om die leesbaarheid en begrip van 'n PIB vir die eerste-linie antiretrovirale (ARV) regimen wat in die Suid-Afrikaanse openbare gesondheidsektor beskikbaar is, te evalueer, en om die aanvaarbaarheid daarvan in 'n teiken-Xhosabevolking te ondersoek. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.